Multidimensional Gender Ideologies Across Europe: Evidence From 36 Countries. Issue 2 (April 2023) - Begall, Katia; Grunow, Daniela; Buchler, Sandra
In this paper, we use the "gender as a social structure" framework to assess macro-, interactional-, and micro-level mechanisms explaining the stalled revolution in gender ideologies. Using the European Values Study 2008 data and latent class analysis, we look at the spread of gender ideologies and examine their association with national levels of gendered ascription of work and care roles, work–family compatibility, social inequality and societal affluence, individual characteristics, and cross-level interactions with gender and education in 36 (post-)industrialized countries. By including a large number of Central, Eastern, and South-Eastern European countries, we provide a new and comprehensive picture of the gender ideology landscapes of Europe, reflected in two unidimensional classes—egalitarian and traditional—and four multidimensional classes, covering more than 60 percent of respondents—family oriented, choice egalitarian, intensive motherhood, and neotraditional. By modeling key features of macro-level variation, we show how the spread of gender ideologies is associated with distinct contextual conditions. We consolidate previous findings on multidimensional gender ideologies, which were based on fewer countries.